Cardiac Arrhythmias as Manifestations of Nanopathies: An Emerging View - Radwański, Przemysław B.; Johnson, Christopher N.; Györke, Sándor; Veeraraghavan, Rengasayee (Frontiers in Physiology, 2018)
Through ongoing research, we are beginning to appreciate that cardiomyocyte nanodomains constitute the functional units for the essential processes of cardiac physiology such as electrical impulse propagation and excitation-contraction coupling. Furthermore, we are recognizing nanodomain dysfunction as the fundamental process underlying life-threatening arrhythmias in a variety of pathologies. Here, we offer an overview of current research on the role of nanodomains in cardiac physiology with particular emphasis on: 1. sodium channel-rich nanodomains within the intercalated disk that participate in cell-to-cell electrical coupling, and 2. dyadic nanodomains located along transverse tubules that participate in excitation-contraction coupling.